Comparison of effectiveness of ginger and metoclopramide on the treatment of nausea and vomiting in pregnancy - Sharief, M.; A. Shaker, S. (Scientific Journal of Medical Science, 2014)
To determine the effectiveness of ginger in comparison to metoclopramide for the treatment of nausea and vomiting in pregnancy. Patients & Methods, It is a comparative randomized prospective trial which has been done at Basrah Maternity and Child Hospital. Sixty three pregnant women with a gestational age between 8-12 weeks who had nausea and vomiting required antiemetic. They had no medical complication and were not hospitalized. Pregnant women were randomly allocated to receive either capsule of 500 mg of ginger plus 400 mcg of folic acid two times /day or 10 mg of metoclopramide three times/ day for 21 days. The degree of nausea and vomiting were assessed by visual analog scale and Likert scale. These were recorded before treatment for base line and after 1 week, 2 weeks, 3 weeks of treatment. Difference of baseline and post treatment nausea, vomiting scores were calculated for both groups during 21 days. All participants except three remained in the study. The visual analog score of post-therapy minus baseline nausea decreased significantly in both groups (2.57±1.7),(1.39±1.6) respectively with more statistically significant with metoclopramide group (P<0.01). The number of vomiting episodes (base line minus average post therapy) in ginger group was 0.73±0.31 compared with (0.97 ± 0.2) in metoclopramide group although there was no significant difference (P>0.24). Likert scales showed 15 cases out of 30 (50%) ginger women reported that their symptoms had improved compared with 20 out of 30 (66%) in metoclopramide group with significant difference between them (P>0.04). No adverse effect of ginger on pregnancy outcome was detected. Ginger is effective for relieving the severity of nausea and vomiting of pregnancy in comparing to the less effective of metoclopramide. Therefore, ginger can be considered as an alternative drug.